Street-Level Enforcement in Urban Communities: Experiences of Cebu City Transportation Office (CCTO) Personnel - Alcontin, Marvin; Sabijon, Dodelon (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study explored the lived experiences of Cebu City Transportation Office (CCTO) personnel in implementing traffic rules and regulations in Cebu City. Guided by a qualitative phenomenological approach, the study aimed to understand the challenges, coping mechanisms, motivations, and aspirations of traffic enforcers in the performance of their duties. Data were gathered through in-depth interviews with selected CCTO personnel who served as the respondents of the study. Thematic analysis was employed to identify recurring patterns and significant themes from the participants’ narratives. The findings revealed that traffic enforcers experienced both fulfillment and hardship in their work. Respondents expressed pride and satisfaction in serving the public and maintaining road safety, while also encountering aggressive motorists, verbal confrontations, threats to personal safety, and insufficient protection during operations. Despite these challenges, the respondents demonstrated professionalism, patience, teamwork, and adherence to established procedures as coping strategies. The study further found that traffic enforcers aspire for stricter implementation of traffic laws, improved public discipline, enhanced infrastructure, and modernization of traffic management systems to promote safer and more efficient road conditions. The study concluded that effective traffic management requires not only committed personnel but also institutional support, public cooperation, and continuous improvement in enforcement systems. It recommends strengthening safety measures, providing continuous professional training, improving inter-agency coordination, and investing in modern traffic management technologies and infrastructure. The study supports Sustainable Development Goal (SDG) 11: Sustainable Cities and Communities by promoting safer and more organized urban transportation systems, and SDG 16: Peace, Justice, and Strong Institutions through the strengthening of public service and law enforcement practices. The sustainability impact of the study lies in its contribution to improving road safety, institutional effectiveness, public discipline, and community well-being through more responsive and efficient traffic management practices.
Keywords: Aggressive Motorists; Cebu City Transportation Office; Public Safety; Road Safety; Traffic Enforcement; Traffic Management; Traffic Violators